2000
DOI: 10.1021/ja000810a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Alkyl Group Effects on the Thermodynamic Stability and Stereochemical Mobility of B(C6F5)3-Derived Zr and Hf Metallocenium Ion-Pairs

Abstract: This paper reports significant dependence of ion-pair formation energetics and stereomutation rates upon the metal-bound alkyl substituent (R) and the solvent dielectric constant in the metallocenium series (1,2-Me2Cp)2MR+ MeB(C6F5)3 - where R = Me, CH2 t Bu, CH2TMS, CH(TMS)2, and M = Zr and Hf, as determined by reaction titration calorimetry and dynamic NMR spectroscopy. For the ion-pair forming reaction, (1,2-Me2Cp)2M(R)Me + B(C6F5)3 → (1,2-Me2Cp)2MR+ MeB(C6F5)3 -, enthalpies in toluene solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 62 publications
7
60
0
Order By: Relevance
“…It can be suggested that the new set of distinct signals belonged to aggregated polynuclear species which were proposed to facilitate undesired side reactions [9]. The formation of polynuclear species was apparently due to an easier ion-pair separation in the more polar CD 2 Cl 2 solvent [10].…”
Section: Resultsmentioning
confidence: 99%
“…It can be suggested that the new set of distinct signals belonged to aggregated polynuclear species which were proposed to facilitate undesired side reactions [9]. The formation of polynuclear species was apparently due to an easier ion-pair separation in the more polar CD 2 Cl 2 solvent [10].…”
Section: Resultsmentioning
confidence: 99%
“…Filtering off the solid residues and the removal of volatiles gave an orange solid, which was washed with 10 ml of light petroleum and dried to afford the orange product 0.20 g (96%). 1 This complex displays a well-documented ion pair symmetrization [11b, 37,38] Complex IV was predominantly formed at Al/Zr ratios of 5-10 after 3-15 min shaking of the NMR tube with ðSBIÞZrCl 2 þ AlBu i 3 þ ½CPh 3 ½BðC 6 F 5 Þ 4 . IV formed a green or blue-green oil in the NMR tube.…”
Section: Nmr Data For Zirconium Complexesmentioning
confidence: 99%
“…Scheme 3) and are rather poor models of the growing polymer chain. Bulkier alkyl ligands give much higher anion exchange rates, e.g., in the series (1,2-Me 2 Cp) 2 Zr(R)(l-Me)B(C 6 F 5 ) 3 (12) the reorganisation enthalpies decrease sharply with increasing bulkiness of the alkyl ligand, R = Me > CH 2 Bu t > CH 2 - [50]. For the ansa-zirconocenes 13, rates for R = CH 2 SiMe 3 are approximately four times higher than for R = Me, with values of ca.…”
Section: Ion Pair Dynamics In Metallocene Catalystsmentioning
confidence: 99%